Social Disfunction Of Students With Diseases Of Cardiovascular System And Principles Of Psychological Correction - Ponomaryov, V.; Alieva, T.; Ryzhenko, M.; Yemets, K. (Psychiatry, Neurology and Medical Psychology, 2016)
This article discusses the principles of psychological correction in patients with diseases of the cardiovascular system , with social functioning disorders . Increased psycho-emotional stressors is a determining factor inthe growth and development of cardiovascular disease. The problems of social functioning of students traditionally are of interest to psychiatrists, psychologists and educators. On the one hand, this is due to the fact that the study period coincides with one of the crisis periods in life, which is the completion of personality. On the other, the educational process has high requirements for the mechanisms of mental adaptation and social functioning.